2012
DOI: 10.1093/humrep/des376
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3B promoter polymorphisms and maternal risk of birth of a child with Down syndrome

Abstract: If confirmed in subsequent studies, DNMT3B promoter polymorphisms might be additional markers to be taken into account when evaluating the contribution of one-carbon (folate) metabolism to the maternal risk of birth of a child with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
2
32
2
1
Order By: Relevance
“…48,49 They are all functional polymorphisms, commonly studied in CRC genetic association studies, and with reported minor allele frequencies ranging from 15% to 49% in healthy Caucasians. [48][49][50] Internal quality control samples with confirmed genotypes were added to each PCR-RFLP reaction. Digestion fragments were visualized after electrophoresis on a 3% agarose gel stained with ethidium bromide.…”
Section: Genotyping Formentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 They are all functional polymorphisms, commonly studied in CRC genetic association studies, and with reported minor allele frequencies ranging from 15% to 49% in healthy Caucasians. [48][49][50] Internal quality control samples with confirmed genotypes were added to each PCR-RFLP reaction. Digestion fragments were visualized after electrophoresis on a 3% agarose gel stained with ethidium bromide.…”
Section: Genotyping Formentioning
confidence: 99%
“…All the analyses were performed with standard protocols at the diagnostic laboratory of the Pisa University Hospital, as detailed elsewhere. 49 Those data are available for a subgroup of the patients (n = 39 for vitamin B12, n = 37 for hcy, and n = 36 for folates) because of blood drawings for biochemical markers was not possible for all of them or for technical problems during analyses, and also because we excluded individuals taking vitamin supplements, metformin, or other drugs known to interfere with those biomarkers.…”
Section: Genotyping Formentioning
confidence: 99%
“…[15], [32][34]. In addition, the functional effects of DNMT3B −579G>T polymorphisms remain to be elucidated; however, few studies have demonstrated the association between this SNP and the risks of acute myeloid leukemia, Down’s syndrome, immune thrombocytopenic purpura, and colorectal cancer [16], [17], [19], [35]. By contrast, no association has been presented between this SNP and the risks of ovarian cancer, breast cancer, and late-onset Alzheimer’s disease [36][38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in a wide range of North American, South American, European, and Asian populations found signi fi cant associations with either MTHFR c.677C>T, c.1298A>C, MTR c.2756C>G, MTRR c.66A>G, CBS 844ins68, and/or SLC19A1 (also known as RFC-1 ) c.80A>G and the risk of having a child with DS. These studies were extensively reviewed in [ 86 ] and can be combined with more recent studies [87][88][89][90][91] . For example, a recent study on another folate pathway-related gene, the DNA methyltransferase gene DNMT3B, found an association between maternal promoter polymorphisms and DS [ 87 ] .…”
Section: Folic Acidmentioning
confidence: 99%
“…These studies were extensively reviewed in [ 86 ] and can be combined with more recent studies [87][88][89][90][91] . For example, a recent study on another folate pathway-related gene, the DNA methyltransferase gene DNMT3B, found an association between maternal promoter polymorphisms and DS [ 87 ] . However, some studies have reported no signi fi cant association between maternal folate pathway polymorphisms and the risk of having a child with DS [92][93][94][95][96] .…”
Section: Folic Acidmentioning
confidence: 99%